Comparison of batch cultivation strategies for cost-effective biomass production of Micractinium inermum NLP-F014 using a blended wastewater medium. (June 2017) - Park, Seonghwan; Kim, Jeongmi; Park, Younghyun; Son, Suyoung; Cho, Sunja; Kim, Changwon; Lee, Taeho
Highlights: A valuable strategy for cost-effective production of M. inermum was determined. Two batch cultivation strategies, fed-batch and sequencing-batch mode, were tested. Culture medium was a mixture of domestic WW and aerobically digested swine WW. The highest biomass productivity was obtained from the sequencing-batch mode. The sequencing-batch mode also showed low environmental impacts. Abstract: Two competitive strategies, fed-batch and sequencing-batch cultivation, were compared in cost-effective biomass production of a high lipid microalgae, Micractinium inermum NLP-F014 using a blended wastewater medium. For fed-batch cultivations, additional nutrient was supplemented at day 2 (FB1) or consecutively added at day 2 and 4 (FB2). Through inoculum size test, 1.0 g-DCW L −1 was selected for the sequencing-batch cultivation (SB) where about 65% of culture was replaced with fresh medium every 2 days. Both fed-batch cultivations showed the maximum biomass productivity of 0.95 g-DCW L −1 d −1, while average biomass productivity in SB was slightly higher as 0.96 ± 0.08 g-DCW L −1 d −1 . Furthermore, remained concentrations of organics (426 mg-COD L −1 ), total nitrogen (15.4 mg-N L −1 ) and phosphorus (0.6 mg-P L −1 ) in SB were much lower than those of fed-batch conditions. The results suggested that SB could be a promising strategy to cultivate M. inermum NLP-F014 with the blended wastewater medium.